2015
DOI: 10.1080/17429145.2015.1015059
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gap microsites and bamboo onAbies faxonianaregeneration in a subalpine forest, China

Abstract: To clarify the effects of gap size and age, as well as microsites on Abies faxoniana recruitment in gaps with or without dwarf bamboo, the occurrences of A. faxoniana seedlings and saplings on four microsites were examined in a subalpine forest in Wanglang Natural Reserve, southwestern China. Results showed that: (1) while increased gap size had little effect on the seedling densities, it significantly reduced the sapling densities on moss-cover ground in A gaps (without bamboos) and those on moss-cover ground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The results also demonstrated that B+ forests are more diverse than that of B-forests. The frequent canopy openings in bamboo forests seem to have provided suitable microsites in the forest floor to establish and grow light-loving species other than those confined to the forest undergrowth (Caccia et al, 2009;Kang et al, 2015;Wang and Liu, 2011), thus increasing the species diversity (Zhang et al, 2013). SIMPER and CA analyses revealed compositional differences between bamboo-and non-bamboo forests further supporting bamboo-driven modifications to these native forests.…”
Section: Discussionmentioning
confidence: 84%
“…The results also demonstrated that B+ forests are more diverse than that of B-forests. The frequent canopy openings in bamboo forests seem to have provided suitable microsites in the forest floor to establish and grow light-loving species other than those confined to the forest undergrowth (Caccia et al, 2009;Kang et al, 2015;Wang and Liu, 2011), thus increasing the species diversity (Zhang et al, 2013). SIMPER and CA analyses revealed compositional differences between bamboo-and non-bamboo forests further supporting bamboo-driven modifications to these native forests.…”
Section: Discussionmentioning
confidence: 84%
“…faxoniana) survives in the cool and wet subalpine region of Sichuan province in southwest China, and its distribution area is also the main habitat of Chinese giant pandas (Ailuropoda melanoleuca David) [43]. It is the dominant tree species of the subalpine coniferous forest [45]. It is naturally distributed from 2700 to 3900 m a.s.l in the subalpine area of Sichuan province [41].…”
Section: Study Areamentioning
confidence: 99%